2006
DOI: 10.1016/j.bbalip.2006.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular localization and tissue-specific distribution of human and yeast DHHC cysteine-rich domain-containing proteins

Abstract: Increasing evidence indicates that DHHC cysteine-rich domain-containing proteins (DHHC proteins) are protein acyltransferases. Although multiple DHHC proteins are found in eukaryotes, characterization has been examined for only a few. Here, we have cloned all the yeast and human DHHC genes and investigated their intracellular localization and tissue-specific expression. Most DHHC proteins are localized in the ER and/or Golgi, with a few localized in the plasma membrane and one in the yeast vacuole.Human DHHC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

37
459
3
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(503 citation statements)
references
References 32 publications
37
459
3
4
Order By: Relevance
“…Immunoblotting with anti-DHHC7 antibody shows that this enzyme is expressed in all colorectal cell lines tested ( Figure 2d). As reported by several studies, we confirmed by immunofluorescence that DHHC7 is expressed in the Golgi apparatus 15,23 (Supplementary Figure S2a), thus suggesting that Fas palmitoylation occurs in this vesicular compartment.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Immunoblotting with anti-DHHC7 antibody shows that this enzyme is expressed in all colorectal cell lines tested ( Figure 2d). As reported by several studies, we confirmed by immunofluorescence that DHHC7 is expressed in the Golgi apparatus 15,23 (Supplementary Figure S2a), thus suggesting that Fas palmitoylation occurs in this vesicular compartment.…”
Section: Resultssupporting
confidence: 89%
“…14 In human, the 23 members of the DHHC family described are localized to the distinct intracellular membrane compartments, mainly the Golgi apparatus and the endoplasmic reticulum where palmitoylation likely occurs. 14,15 Since their discovery in 2002, increasing numbers of DHHC-substrate pairs have been identified allowing a deeper comprehension of palmitoylation regulation. 16 Fas palmitoylation occurs on an intracellular cysteine adjacent to the transmembrane domain (cysteine 199 in human) and is critical for its ability to trigger cell death.…”
mentioning
confidence: 99%
“…We exploited a genetically sensitized form of HMR silencing and identified PFA4, a gene that encodes a DHHC (asp-his-his-cys) domain-containing, integral membrane S-palmitoyltransferase of the endoplasmic reticulum (ER) (11,12). The data supported a model in which Pfa4 modulated HM silencing, Sir-complex dynamics, and macromolecular aspects of telomere architecture by palmitoylating the telomere binding protein Rif1.…”
supporting
confidence: 51%
“…The development of specific inhibitors of PATs is restricted by the high level of conservation among PATs in eukaryotic species and the conserved use of palmitoyl-CoA as a substrate (Ducker et al, 2006). Furthermore, it has been shown that a high level of redundancy exists, so that without targeting all, or at least the majority, of PATs, little effect will probably be observed (Ohno et al, 2006;Roth et al, 2006). The situation is clearly different in T. gondii, where five putative PATs appear to be essential for parasite survival, with the indispensability of TgDHHC7 being experimentally proven by the failure in propagating the mutant with a DiCre excised gene (Frenal et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As in humans and yeast (Ohno et al, 2006), these DHHCs are targeted to distinct endomembrane compartments, with several of them found in the Golgi apparatus (Table 2). In addition, some enzymes are found at the PM and in the apicomplexan-specific organelles including the IMC and the rhoptries.…”
Section: Enzymes Implicated In Protein Palmitoylationmentioning
confidence: 99%